1996
DOI: 10.2466/pr0.1996.78.1.271
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Review of Research on Charismatic Leadership

Abstract: This study used meta-analysis to explore the relationship between charismatic leadership and satisfaction with the leader, perceived leader's effectiveness, and performance. To maintain construct consistency Bass' 1985 conceptualization of charisma was used. Results indicate potential moderating effects for two moderators of research design (objective/subjective performance and percept-percept/multisource study design) and for two theoretically predicted moderators (organizational level of focal leader and org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
206
2
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(221 citation statements)
references
References 49 publications
7
206
2
6
Order By: Relevance
“…Transformational leaders are valuable to organizations because as meta-analytical studies have shown, transformational leadership is associated with leader effectiveness and follower satisfaction with their leader (Fuller, Patterson, Hester, & Stringer, 1996;Judge & Piccolo, 2004). Furthermore, and probably most importantly in the current economy, transformational leaders are able to enhance their followers' in-role and extra-role performance (Lowe, Kroeck, & Sivasubramaniam, 1996).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Transformational leaders are valuable to organizations because as meta-analytical studies have shown, transformational leadership is associated with leader effectiveness and follower satisfaction with their leader (Fuller, Patterson, Hester, & Stringer, 1996;Judge & Piccolo, 2004). Furthermore, and probably most importantly in the current economy, transformational leaders are able to enhance their followers' in-role and extra-role performance (Lowe, Kroeck, & Sivasubramaniam, 1996).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…This trust and loyalty result in followers willing to commit to the organization even under very difficult circumstances [52]. Other empirical studies also showed positive relationships between transformational leadership and personal outcomes such as satisfaction and performance of followers [53], [54], [48]. There is a clear need for greater attention in this area to understand the mechanisms through which transformational leadership influences personal attitudes in order to develop a more complete understanding of the inner workings of transformational leadership.…”
Section: ) Transformational Leadership Effectivenessmentioning
confidence: 99%
“…They display self-confidence and are able to inspire followers to transcend their own self-interest for the sake of the collective (e.g., Bass, 1985;House, 1977House, , 1996Shamir, House, & Arthur, 1993). Meta-analyses have shown that charismatic leadership correlates positively with a wide range of variables (e.g., Fuller, Patterson, Hester, & Stringer, 1996;Lowe, Kroeck, & Sivasubramaniam, 1996), including organizational commitment (e.g., Bycio, Hackett, & Allen, 1995), personal identification (Shamir, Zakay, Breinin, & Popper, 1998), and firm profitability (e.g., De Hoogh et al, 2004;Waldman et al, 2001). Previous research has also suggested that charismatic leadership elicits OCB from followers.…”
Section: Charisma and Belongingnessmentioning
confidence: 99%